2017
DOI: 10.1007/s11010-017-3043-8
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA CCAT1 inhibits cell apoptosis of renal cell carcinoma through up-regulation of Livin protein

Abstract: This study was to investigate the involvement of long non-coding RNA (lncRNA) colon cancer-associated transcript-1 (CCAT1) in renal cell carcinoma (RCC) and to further uncover its underlying mechanism. In this study, the expression of CCAT1 and Livin of RCC tissues or cells was determined using qRT-PCR (quantitative real-time PCR) and western blot, respectively. RNA pulldown and RIP (RNA-Binding Protein Immunoprecipitation) assays were performed to examine the sequence interaction between CCAT1 and Livin. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…23 Likely, CCAT1 regulates EGFR expressions in SCC cells. 24 As a fundamental function by IncRNA, CCAT1 can regulate expressions of many miRNAs, including miR-143, miR-155, miR-181a, and miR-218-5p. 24 As a fundamental function by IncRNA, CCAT1 can regulate expressions of many miRNAs, including miR-143, miR-155, miR-181a, and miR-218-5p.…”
Section: Discussionmentioning
confidence: 99%
“…23 Likely, CCAT1 regulates EGFR expressions in SCC cells. 24 As a fundamental function by IncRNA, CCAT1 can regulate expressions of many miRNAs, including miR-143, miR-155, miR-181a, and miR-218-5p. 24 As a fundamental function by IncRNA, CCAT1 can regulate expressions of many miRNAs, including miR-143, miR-155, miR-181a, and miR-218-5p.…”
Section: Discussionmentioning
confidence: 99%
“…But due to the growing depth of sequencing technology, more and more new lncRNAs have been found to be involved in various physiological and pathological processes [5]. Studies have shown that a number of lncRNAs are abnormally expressed in many tumours and may be involved in multiple processes of tumorigenesis and development, including cell differentiation and proliferation, cell cycle regulation, invasion and metastasis [6][7][8]. Thus, lncRNAs have been regarded as new biomarkers in various cancers including RCC.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed that CCAT1 knockdown reduces cell viability in various cancers, including renal cell carcinoma, glioma, melanoma and retinoblastoma [16,[20][21][22]. Herein, CCAT1 expression was knocked down in two GC cell lines and the effects of CCAT1 knockdown on cell viability, colony formation ability and cell cycle progression were investigated.…”
Section: Discussionmentioning
confidence: 98%